The legal technique of the Land Code of the USSR in 1922, the Law «On Forests USSR» of 1923, the Mining Code of the USSR in 1928 - Patlachuk, Oleksandr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article considers the legal technique adopted in the 20-30-ies. the last century codified acts, which regulated the protection of natural objects. It shows the existence of a very complex system of hierarchical construction of three acts, sections that do not have division into chapters, and also a non-uniform distribution of material in the middle of codified acts. It is proved that the largest in terms of the volume and number of articles is the Land Code of the Ukrainian SSR in 1923, and the greatest number of questions of legal responsibility is fixed in the Mountain Code of the Ukrainian SSR in 1928, which is almost 6,2% of the total amount of material